Studi Literatur : Pemanfaatan Web Wordwall Untuk Melatih Kemampuan Computational Thinking Siswa Dalam Pembelajaran Matematika - Salwa Sausan; Suryani Sirait; Salihin Salihin; Rosliana Siregar (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to analyze the effect of using Web Wordwall in training students' computational thinking skills in mathematics learning with a qualitative approach. The research subject is the Director General of Teachers and Education Personnel, while the object is education that is liberating and pro-student. Data obtained from online and offline information sources is recorded in a structured manner, then analyzed to be synthesized into a systematic conceptual framework. Conclusions are drawn by taking the essence of the conceptual framework that can answer the research questions posed. The research method used is a case study with a focus on participatory observation, in-depth interviews and document analysis. Data was collected through literature study and analysis of learning materials. Data analysis was carried out using an inductive approach, by looking for patterns of findings and main concepts from the data collected.